2022
DOI: 10.1094/phyto-08-21-0345-r
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Fungi of an Ambrosia Beetle Alter the Volatile Bouquet of Cork Oak Seedlings

Abstract: In Portugal, fungal symbionts of the ambrosia beetle Platypus cylindrus affect tree vigor of cork oak (Quercus suber) and are linked with the cork oak decline process. Fungal symbionts play crucial roles in bark and ambrosia beetles life history and recent work indicates complex interactions on the fungal and plant metabolic level. Colonized trees may respond with an array of currently unknown volatile metabolites being indicative of such interactions, acting as infochemicals with their environment. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Therefore, the conversion of monoterpenes to their less toxic oxygenated derivatives by fungal symbionts could reduce the extent of monoterpene toxicity to MPB. Earlier studies reported a similar detoxification mechanism by fungal symbionts of several bark beetle species [ 10 , 44 ]. Auto-oxidation of monoterpenes can also occur as the resin encounter air; however, in this study, we found the concentrations of several oxygenated monoterpenes such as borneol and terpinene-4-ol were multiple folds higher in the fungal treated tissues compared to the control, suggesting the possible role of fungi in the detoxification process.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, the conversion of monoterpenes to their less toxic oxygenated derivatives by fungal symbionts could reduce the extent of monoterpene toxicity to MPB. Earlier studies reported a similar detoxification mechanism by fungal symbionts of several bark beetle species [ 10 , 44 ]. Auto-oxidation of monoterpenes can also occur as the resin encounter air; however, in this study, we found the concentrations of several oxygenated monoterpenes such as borneol and terpinene-4-ol were multiple folds higher in the fungal treated tissues compared to the control, suggesting the possible role of fungi in the detoxification process.…”
Section: Discussionmentioning
confidence: 71%
“…Our research objectives are (1) to investigate the host terpene detoxification by MPBs’ fungal symbionts [ 38 , 44 , 45 ]; (2) to determine the benefits of maintaining multiple species of fungal symbionts to MPBs; (3) to test whether MPB elicits behavioral responses to FVOCs produced its fungal symbionts. Here, we inoculated the mature lodgepole pine trees in a forest stand with three fungal species ( G. clavigera, L. longiclavatum, and O. montium ) of MPB.…”
Section: Introductionmentioning
confidence: 99%
“…It was found recently that strains of fungal associates of P. cylindrus , which is a major cork oak pest in Portugal, induced an increase in volatiles known for mediating ambrosia beetle behavior (mainly acetophenone, sulcatone, and nonanal) in response to fungal inoculation. This may help to elucidate the mutualistic or pathogenic aspects of these complex symbiotic interactions and develop new control strategies for P. cylindrus [ 48 ].…”
Section: Acetophenone Is a Prolific Semiochemical For Plant-feeding I...mentioning
confidence: 99%
“…Inoculation of cork oak with Raffaelea montetyi , R. quercina , and Ceratocystiopsis sp. nov., four fungi farmed by ambrosia beetles during their establishment within the host plant, leads to a reduction in the host biosynthesis of monoterpenes, possibly as a means of controlling plant immunity (Nones et al 2022 ). Fungal colonization can also systemically affect terpene synthesis (Sarkar and Sadhukhan 2023 ).…”
Section: Introductionmentioning
confidence: 99%